2009
DOI: 10.1098/rstb.2008.0286
|View full text |Cite
|
Sign up to set email alerts
|

Predicting invasion success in complex ecological networks

Abstract: A central and perhaps insurmountable challenge of invasion ecology is to predict which combinations of species and habitats most effectively promote and prevent biological invasions. Here, we integrate models of network structure and nonlinear population dynamics to search for potential generalities among trophic factors that may drive invasion success and failure. We simulate invasions where 100 different species attempt to invade 150 different food webs with 15-26 species and a wide range (0.06-0.32) of conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
165
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(182 citation statements)
references
References 67 publications
(195 reference statements)
16
165
1
Order By: Relevance
“…We found that more connected food webs are more vulnerable to invasions. This contrast with previous theoretical results by Romanuk et al (2009), where the authors found that more connected food webs were more robust to invasions. These opposite results may arise from the relationship between species richness and connectance in both studies.…”
Section: Discussion Complexity and Robustness To Invasionscontrasting
confidence: 99%
See 4 more Smart Citations
“…We found that more connected food webs are more vulnerable to invasions. This contrast with previous theoretical results by Romanuk et al (2009), where the authors found that more connected food webs were more robust to invasions. These opposite results may arise from the relationship between species richness and connectance in both studies.…”
Section: Discussion Complexity and Robustness To Invasionscontrasting
confidence: 99%
“…These values were chosen because they fall well within the values of the distribution from which the initial biomasses of species in the communities were taken (see Supplementary Material S2). These were considerably lower that those employed in other studies that have used the same model for population dynamics employed here (Romanuk et al, 2009), in order to account for the fact that invasive species are usually less abundant than those in the native community. This allowed us to investigate the effect of propagule pressure on invasion success.…”
Section: In Silico Invasion Experimentsmentioning
confidence: 72%
See 3 more Smart Citations